GeTe: a simple compound blessed with a plethora of properties. Issue 36 (7th September 2017) - Boschker, Jos E.; Wang, Ruining; Calarco, Raffaella
Abstract : A selection from the wide range of functional properties present in the binary compound, GeTe, are reviewed is this paper. Abstract : GeTe is a rather unconventional and complex compound from a fundamental point of view considering its very simple stoichiometry. Within this review, we first discuss the crystal structure of GeTe, focusing our attention on the bonding mechanism and on the distortion of the unit cell. This distortion is responsible for the ferroelectric properties of GeTe that are also considered here. Furthermore, we describe the amorphous phase and review the phase change material properties resorting to examples from several GeTe based alloys. Finally we examine the usage of GeTe for spintronics, a fairly recent application field.